Health literacy action framework for health emergencies and infodemics - Okan, Orkan; Messer, Melanie; Levin-Zamir, Diane; Dadaczynski, Kevin; Paakkari, Leena; Schaeffer, Doris; Sorensen, Kristine (Information services & use, 2023)
This paper addresses the critical role of health literacy during the COVID-19 infodemic and provides recommendations for decision-makers regarding how health literacy can be advanced as an empowering resource to mitigate the harmful effects of future infodemics. Based on a comprehensive literature review, key areas concerning health literacy are identified that help provide a strategic response during an infodemic. A framework for systemic health literacy capacity and policy advice is presented to inform and guide decision-makers on managing an infodemic with health literacy strategies. The way forward includes emphasizing the rights to access information and a broader view of how health literacy can help build back better in the aftermath of the COVID-19 pandemic. Finally, the paper includes a call to action for decision-makers to integrate systemic health literacy responsiveness into public health emergency strategies to counter a future infodemic’s diffusion.